2019
DOI: 10.1001/jamaneurol.2019.0648
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early-Onset Alzheimer Disease With Elevated Low-Density Lipoprotein Cholesterol Levels and Rare Genetic Coding Variants of APOB

Abstract: IMPORTANCE Early-onset Alzheimer disease (EOAD) is a rare form of Alzheimer disease (AD) with a large genetic basis that is only partially understood. In late-onset AD, elevated circulating cholesterol levels increase AD risk even after adjusting for the apolipoprotein E ε4 (APOE E4) allele, a major genetic factor for AD and elevated cholesterol levels; however, the role of circulating cholesterol levels in EOAD is unclear. OBJECTIVES To investigate the association between circulating cholesterol levels and EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 47 publications
8
77
1
2
Order By: Relevance
“…However, whether elevated LDL-c level is related to the risk of AD remains unconfirmed. Several studies reported that patients with AD exhibited higher level of LDL-c when compared with normal controls (Lesser et al, 2009;Wingo et al, 2019). In contrast, some of the studies detected no significant difference in LDL-c level between AD patients and healthy controls (Davidson et al, 2012;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, whether elevated LDL-c level is related to the risk of AD remains unconfirmed. Several studies reported that patients with AD exhibited higher level of LDL-c when compared with normal controls (Lesser et al, 2009;Wingo et al, 2019). In contrast, some of the studies detected no significant difference in LDL-c level between AD patients and healthy controls (Davidson et al, 2012;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these data provided evidences that ApoB and APOEε4 status may contribute to the changes of CSF AD core biomarkers, independently of each other. However, a recent study found that rare genetic coding variants of APOB gene were strongly associated with familial AD, which indicated that APOB gene might also harbor protective and deleterious variants in sporadic AD similar to the APOEε2 and APOEε4 alleles (35). Identifying such a protective coding variant of APOB gene would greatly strengthen the link between ApoB and AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…High total and low-density-lipoprotein cholesterol (LDL-C) levels during midlife were most consistently associated with chances of future dementia [ 96 ]. A recent study reported that early-onset AD patients have high LDL-C levels and 3% of them harbor rare variants in the APOB gene [ 97 ], providing both epidemiological and biological links between aberrant cholesterol metabolism and AD. Furthermore, hypercholesterolemia associated with a heavier burden of AD pathology and cerebral amyloid angiopathy in autoptic cases [ 98 ], while animal models of AD showed worsening of Aβ accumulation and cognitive deficits upon diet-induced hypercholesterolemia [ 99 ].…”
Section: Roles Of Diet and Microbiota In Neurodegenerative Diseasementioning
confidence: 99%